The Mediterranean mussel Mytilus galloprovincialis: responses to climate change scenarios as a function of the original habitat. Issue 1 (4th February 2021) - Lassoued, Jihene; Padín, X A; Comeau, Luc A; Bejaoui, Nejla; Pérez, Fiz F; Babarro, Jose M F
Abstract : The responses of two very distinct populations of the same marine mussel species Mytilus galloprovincialis, and inhabiting the Atlantic and Mediterranean Seas, were evaluated facing climate change scenarios with regard to p CO2 and temperature drivers. The potential threats and resilient behaviour of individuals according to their original habitat were drawn and discussed. Abstract: The impact of simulated seawater acidification and warming conditions on specimens of the mussel Mytilus galloprovincialis locally adapted to very distinct, widely separated sites in the Mediterranean Sea (Tunisia) and Atlantic Sea (Galicia, NW Spain) was evaluated in relation to key behavioural and eco-physiological parameters. Over the 2-month exposure to the experimental conditions, mussels were fed optimally to ensure that there are no synergistic interactions between climate change drivers and energetic status of the individuals. In general, regardless of origin (Atlantic or Mediterranean), the mussels were rather resilient to acidification for most of the parameters considered and they were able to grow in strongly acidified seawater through an increased feeding activity. However, shell strength decreased (40%) consistently in both mussel populations held in moderately and highly acidified seawater. The observed reduction in shell strength was not explained by slight alterations in organic matter, shell thickness or aragonite:calcite ratio. The combined effects of high acidification and warming on the key response of byssus strength caused a strong decline in mussel performance, although only in Galician mussels, in which the valve opening time decreased sharply as well as condition index (soft tissue state) and shell growth. By contrast, the observed negative effect of highly acidified scenario on the strength of Tunisian mussel shells was (partly but not totally) counterbalanced by the higher seawater temperature. Eco-physiological and behavioural interactions in mussels in relation to climate change are complex, and future scenarios for the ecology of the species and also the feasibility of cultivating them in Atlantic and Mediterranean zones are discussed.